Critique of zeroness: understanding Deleuze’s (mis)understanding of Peirce - Fernandes, Daniele (Cognitio-Estudos: revista eletrônica de filosofia, 2019)
This article aims to explore the relation between Deleuze and Peirce, from what seems to be the main point of confrontation between them: Deleuze’s statement that there would be a zeroness before Peirce’s firstness. Specifically, the aim is to criticize this statement in two ways: an exogenous one, based on the critique of Deleuze’s understanding of Peirce’s work; another endogenous, based on Deleuze’s own concepts and comments. The hypothesis is that there is no a deep conceptual divergence. The key to understand this statement lies in how Deleuze’s limited knowledge on Peirce’s theory led him to frame firstness into his own philosophical work and to disregard a Peircian concept that would be more adequate than zeroness.